(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to examine the methods and content of the provisions in the American Association of Blood Banks (AABB) standards for guaranteeing quality and safety in blood banks and biological therapies. Method: The research was done by synthesising and analysing papers from AABB standards, FDA materials, and the United States Code of Federal Regulations in health and clinical laboratory services. Results: Currently, roughly 90 facilities worldwide have gained AABB certification. To be recognised, units must undergo a rigorous evaluation procedure consisting of two phases: a self-assessment and direct on-site evaluation based on a strict set of requirements that includes ten quality system elements. Conclusion: AABB certification is critical for improving service quality and patient safety. It serves not only as a measure of compliance with international rules but also as a motivator for blood banks and biological therapies to enhance service quality for the benefit of the community continuously.